Analytic of VSC-HVDC Interconnected Power Systems from a Perspective of Frequency Security. Issue 1 (February 2021) - Zhu, Liuzhu; Ma, Jing; Xu, Jiayin; Shen, Yuming; Zhang, Enhui; Luo, Xuzhi; Mao, Fubin; Wang, Lijun; Xia, Kai; Yang, Mengmeng
Abstract: In the interconnected power systems with VSC-HVDC (Voltage Source Converter-High Voltage Direct Current) transmission links, the failures of VSC-HVDC system can cause large power imbalance for both sending-end and receiving-end power systems. In this paper, the reliability model of the VSC-HVDC system is developed based on series-parallel structure recognition. The frequency dynamics of the power systems are characterized considering the frequency regulation of the power systems in response to the power imbalance arise from the component failures. Moreover, the Monte Carlo simulation method is applied to analyze the frequency dynamics in different contingencies. The indices measuring the frequency stability and the reliability of the interconnected power systems are introduced.